Can lymphovascular invasion replace the prognostic value of lymph node involvement in patients with upper tract urothelial carcinoma after radical nephroureterectomy? - Yoo, Eun Sang; Ha, Yun-Sok; Lee, Jun Nyung; Kim, Bum Soo; Kim, Bup Wan; Byun, Seok-Soo; Choi, Young Deuk; Kang, Ho Won; Yun, Seok-Joong; Kim, Wun-Jae; Kim, Jeong Hyun; Kwon, Tae Gyun (Canadian Urological Association Journal, 2016)
Introduction: This study aimed to evaluate whether lymphovascular invasion (LVI) can replace lymph node (LN) involvement as a prognostic marker in patients who do not undergo lymph node dissection (LND) during surgery in patients with upper tract urothelial carcinoma (UTUC). Methods: A total of 505 patients who underwent radical nephroureterectomy (RNU) were recruited from four academic centres and divided into four groups: node negative (N0, Group 1); node positive (N+, Group 2); no LND without LVI (NxLVI-, Group 3); and no LND with LVI (NxLVI+, Group 4). Results: Patients in Group 2 had larger tumours, a higher incidence of left-sided involvement, more aggressive T stage and grade, and a higher positive surgical margin rate than patients in other groups. Pathological features (T stage and grade) were poorer in Group 4 than in Groups 1 and 3. Compared to other groups, Group 2 had the worst prognostic outcomes regarding locoregional/distant metastasis-free survival (MFS), cancer-specific survival (CSS), and overall survival (OS). LVI and LN status in Group 4 was not associated with MFS in multivariate analysis. Among Nx diseases, LVI was not an independent predictor of MFS or CCS. The small number of cases in Groups 2 and 4 is a major limitation of this study. Conclusions: Clinical outcomes according to LVI did not correlate with those outcomes predicted by LN involvement in patients with UTUC. Therefore, LVI may not be used as a substitute for nodal status in patients who do not undergo LND at the time of surgery.